2017
DOI: 10.1128/jvi.00735-17
|View full text |Cite
|
Sign up to set email alerts
|

Replication of JC Virus DNA in the G144 Oligodendrocyte Cell Line Is Dependent Upon Akt

Abstract: Progressive multifocal leukoencephalopathy (PML) is an often-fatal demyelinating disease of the central nervous system. PML results when oligodendrocytes within immunocompromised individuals are infected with the human JC virus (JCV). We have identified an oligodendrocyte precursor cell line, termed G144, that supports robust levels of JCV DNA replication, a central part of the JCV life cycle. In addition, we have determined that JC virus readily infects G144 cells. Furthermore, we have determined that JCV DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…Given the specificity of the virus to the human host, in vitro systems using human cell lines are critical for understanding viral infection and pathogenesis. Previous to this study, JCPyV infection in vitro has been limited to cell types found in human brain parenchymal cells, including the cell lines derived from human fetal glial cells, SVG and SVG-A (60-63), progenitor-derived astrocytes (64)(65)(66), hESC-derived oligodendrocyte progenitors (67), glial progenitor cells and astrocytes (68), and a recently described glioblastoma-derived oligodendrocyte precursor line (69). These cells do not always proliferate well and have varying degrees of virus susceptibility.…”
Section: Figmentioning
confidence: 99%
“…Given the specificity of the virus to the human host, in vitro systems using human cell lines are critical for understanding viral infection and pathogenesis. Previous to this study, JCPyV infection in vitro has been limited to cell types found in human brain parenchymal cells, including the cell lines derived from human fetal glial cells, SVG and SVG-A (60-63), progenitor-derived astrocytes (64)(65)(66), hESC-derived oligodendrocyte progenitors (67), glial progenitor cells and astrocytes (68), and a recently described glioblastoma-derived oligodendrocyte precursor line (69). These cells do not always proliferate well and have varying degrees of virus susceptibility.…”
Section: Figmentioning
confidence: 99%
“…The PI3K/AKT/mTOR signaling pathway has been previously implicated in other polyomavirus infections as well [48,50,59,[89][90][91][92]. Earlier research has demonstrated that the BK polyomavirus (BKPyV), murine polyomavirus, and JCPyV influence the PI3K/AKT signaling pathway by modulating the cellular phosphatase, protein phosphatase 2A (PP2A) [89][90][91].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the PI3K/AKT/mTOR signaling pathway implicated in JCPyV infection [48,50,59], the mitogen-activated protein kinase, extracellular signal-regulated kinase (MAPK/ERK) pathway is required for JCPyV infection [61,73,74]. This pathway is temporally regulated, specifically being phosphorylated upon JCPyV infection, and infection of immortalized cells is significantly reduced when cells are treated with ERK siRNAs or inhibitors [61,66,73,74].…”
Section: U0126 a Common Mek Inhibitor Does Not Reduce Jcpyv Infection...mentioning
confidence: 99%
See 2 more Smart Citations